Tindak Tutur dalam Pembelajaran Bahasa Indonesia Kelas VII SMP Nahdatul Ulama Bogor - Siti Mualamah; Siti Robiah; Sopi Robiah; Risky Yulia Nurarifin; Nunung Nuraini; Irwan Siagian (Journal on Education, 2023)
The purpose of this study was to determine the use of speech acts in learning activities. The object of study in this study were teachers and students, the data in this study were locutionary speech acts, illocutionary speech acts, and perlocutionary speech acts. This research method or technique uses a qualitative descriptive method. because this type of method is more appropriate for finding problems that require more in-depth study. From the results of this study, we can see that the speech acts found in class VII Indonesian SMP Nahdlatul Ulama are locutionary, illocutionary, and perlocutionary speech acts. The speech acts found were in the form of illocutionary orders, questions, and news. The illocutionary speech acts found are assertive, declarative, directive, and expressive speech acts. Meanwhile, the perlocutionary speech act found is influencing.